2021
DOI: 10.1186/s40317-021-00238-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating receiver contributions to acoustic positional telemetry: a case study on Atlantic cod around wind turbines in the North Sea

Abstract: Background The effect of individual acoustic receiver contributions to animal positioning is a crucial aspect for the correct interpretation of acoustic positional telemetry (APT). Here, we evaluated the contribution of each receiver within two APT designs to the number of tag signals detected and the position accuracy of free-ranging Atlantic cod, through data exclusion of single receivers from the analysis. The two APTs were deployed around offshore (ca 50 km) wind turbines at which 27 indivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Van der Knaap et al (2021) also found behavioural effects for the fish that stayed during the seismic survey as these individuals spent significantly less time being locally active (likely including foraging behaviour) and switched to being more inactive. Although Van der Knaap et al (2021) did not find a clear dose-response pattern, they did reveal that the daily rhythm of the cod in activity fluctuations as observed during days without survey was disrupted during the sound exposure.…”
Section: Seismic Survey Exposure Conditions and Potential Consequencesmentioning
confidence: 72%
See 4 more Smart Citations
“…Van der Knaap et al (2021) also found behavioural effects for the fish that stayed during the seismic survey as these individuals spent significantly less time being locally active (likely including foraging behaviour) and switched to being more inactive. Although Van der Knaap et al (2021) did not find a clear dose-response pattern, they did reveal that the daily rhythm of the cod in activity fluctuations as observed during days without survey was disrupted during the sound exposure.…”
Section: Seismic Survey Exposure Conditions and Potential Consequencesmentioning
confidence: 72%
“…We collected our acoustic recordings in Belgian territorial waters in the southern part of the North Sea (51.670 N, 2.802 E). The area is a shallow continental shelf sea with depths of less than 45 m. We deployed the recording equipment in the southwest corner of Belwind wind farm, situated on the Bligh Bank at the marine border between Belgium and the Netherlands (Brabant et al, 2013;Van der Knaap et al, 2021), about 50 km offshore (see Fig. 1).…”
Section: A Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations